USING TICKING OFF ITEMS TECHNIQUE IN THE TEACHING LISTENING SKILL AT ELEMENTARY STUDENT - Fitri Annisa (MADROSATUNA : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2018)
Listening skill is the first skill that should be mastered by young learners when they learn language besides speaking, reading and writing skill. English in In Indonesia is still considered as difficult subject at school. Especially in listening, most of student especially young learners get difficulties to comprehend what is spoken in English. It is natural thing when they do not comprehend because English is a foreign language. English course, whether as a local conten, a compulsary or an extra-curicullar subject at elementary School, is given to equip students with English so they an enhance communicative competence in language accompaniying action on a simple basis in the context of school and give awareness the importance of English language to improve competitiveness in a global society. Most of elementary school dont have any tape recorder yet, which contain English speaking by native language or the expert of English language. Thus, EYL teachers have important role as the sources of teaching and learning. This is because the students are able to listen the teacher`s talk directly. In addition, teacher should be more creative teaching listening to young learners, in other the students are not boring.